The Development of Students’ Worksheet Based on Predict-Observe-Explain (POE) - Riska Mulyani; Saminan Saminan; Sulastri Sulastri (Proceedings of AICS - Social Sciences, 2017)
The research and development have been done to develop student worksheets (LKPD) based on predicting, observing, and explaining (POE). The development research model used refers to the ADDIE development model which consists of 5 stages: analysis, design, development, implementation, and evaluation. The assessment of product quality of LKPD development results carried out by validator and 14 physics teachers. The percentage of eligibility obtained from each validator and physics teacher is 77% and 83%. The test implementation of LKPD products applied to 20 students of class X MIA 2 SMAN 3 Unggul Sigli that chosen by purposive sampling. The results of a POE-based LKPD testing can improve the students’ critical thinking skills. Based on these results, it can be concluded that POE-based LKPD developed with the ADDIE development model is decent to be implemented. An investigation on a broader scale should be undertaken to assess the effectiveness in teaching physics.